Tratamiento con nanoestructuras en un perro con Alopecia X (Veterinary Science, 2025)
Alopecia X is considered a non-inflammatory pathology, without systemic signs, characterized by the arrest of the hair cycle, common in the Pomeranians, but may occur in other breeds. A healthy, neutered Pomeranian female was treated with hair cycle arrest confirmed for alopecia X and skin dryness. The treatment consisted of a hair spray formulation composed of physiologically balanced growth factors in an alcohol-free aqueous-based solution, with the purpose of stimulating the hair follicle and consequently hair growth. Another composition of moisturizing and nourishing active ingredients was selected for the treatment of dry skin. This promising therapy is easy to administer, has no side effects and is low cost, emerging as an alternative to therapies that cause skin trauma and administration of systemic medications, often without success.
Keywords: Alopecia X, IGF, VEGF, bFGF, Nano copper peptide